2013
DOI: 10.1242/bio.20135546
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol exposure disrupts extraembryonic microtubule cytoskeleton and embryonic blastomere cell adhesion, producing epiboly and gastrulation defects

Abstract: SummaryFetal alcohol spectrum disorder (FASD) occurs when pregnant mothers consume alcohol, causing embryonic ethanol exposure and characteristic birth defects that include craniofacial, neural and cardiac defects. Gastrulation is a particularly sensitive developmental stage for teratogen exposure, and zebrafish is an outstanding model to study gastrulation and FASD. Epiboly (spreading blastomere cells over the yolk cell), prechordal plate migration and convergence/extension cell movements are sensitive to ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 47 publications
(87 reference statements)
0
41
0
Order By: Relevance
“…Our laboratory previously showed that treating zebrafish embryos with lower ethanol concentrations (0.6 and 0.9% v/v) produced reproducible defects in gastrulation cell movements, cell adhesion, and heart morphogenesis (Marrs et al, 2010; Sarmah & Marrs, 2013; Sarmah et al, 2013). Abnormal retinal cell differentiation events may be due to a combination of increased oxidative stress, increased cell death, disrupted cell signaling pathways, and altered epigenetic modifications induced by ethanol exposure (Muralidharan, Sarmah, Zhou, & Marrs, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory previously showed that treating zebrafish embryos with lower ethanol concentrations (0.6 and 0.9% v/v) produced reproducible defects in gastrulation cell movements, cell adhesion, and heart morphogenesis (Marrs et al, 2010; Sarmah & Marrs, 2013; Sarmah et al, 2013). Abnormal retinal cell differentiation events may be due to a combination of increased oxidative stress, increased cell death, disrupted cell signaling pathways, and altered epigenetic modifications induced by ethanol exposure (Muralidharan, Sarmah, Zhou, & Marrs, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…RNA isolation and quantitative PCR analysis were performed as previously described (Sarmah et al, 2013) for 72 hpf treated and untreated embryos. The primers for rhodopsin and red opsin were used as previously described (Laranjeiro & Whitmore, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The Wnt/PCP pathway is critical for regulating convergent/extension movements in the early embryo that elongate the body axis, and separate the eye fields in zebrafish. There are several reports of ethanol disrupting convergent/extension movements (Sarmah et al, 2013; Yelin et al, 2005). Thus, it is likely that combined genetic and environmental inhibition of Wnt/PCP signaling is responsible for the vangl2 -ethanol interaction, yet the mechanism by which ethanol may inhibit Wnt/PCP signaling remains to be determined.…”
Section: Fasd Geneticsmentioning
confidence: 99%
“…Sox2 and other Sox B1 type transcriptional regulators control a wide range of developmental effectors, including pcdh18a (gastrulation movement), neurog1, hesx1, and zic1 (neural differentiation), oep, and shh (neural patterning) 29 . Our previous Affymetrix GeneChip microarray study (GEO accession: GSE48380) comparing genes in control and ethanol-exposed embryos during mid-gastrulation identified significant dysregulation of all these genes after ethanol exposure at 8 hpf 15,22 . Reduction of Sox2 prior to gastrulation might be responsible for the dysregulation of these genes, interfering with gastrulation and other developmental events.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies provided evidence of critical signaling dysregulation during organogenesis, including BMP, Notch, Wnt, and retinoic acid, which leads to heart and eye defects 18,20 . Phenotypic differences between ethanol-treated and untreated embryos were first detected during gastrulation, when ethanol-treated embryos displayed reduced epiboly progression [22][23][24] . Our studies examining changes in gene expression in ethanol-exposed embryos at mid-gastrulation (8 hpf) using microarray gene expression analysis identified various dysregulated genes including cell adhesion molecule Protocadherin-18a 22 .…”
mentioning
confidence: 99%